QGA-based network service extension algorithm in NFV - Hang QIU; Hongbo TANG; Wei YOU; Yu ZHAO; Yi BAI (Tongxin xuebao)
To meet the client’s new business requirements or add additional security protection functions, the already hosted network service extension problem in the cloud network based on network function virtualization was researched.The network service extension in the cloud network was modeled as an integer linear programming, considering the impact on initial service, extended graph deployment, resource capacity and virtual network function affinity constraints, and so on.To deal with the computational complexity and dynamism of future large-scale cloud networks, a QGA-based network service extension algorithm was proposed to improve solution efficiency and solution quality through quantum parallel computing.Simulation results prove that the efficient performance of the proposed algorithm in terms of extension successful ratio and average resource costs, and the proposed algorithm has low time complexity.